2021
DOI: 10.1590/0102-672020210002e1626
|View full text |Cite
|
Sign up to set email alerts
|

Obesidade E Esteatose Grave: A Importância Da Avaliação Bioquímica E Escores

Abstract: RESUMO - RACIONAL: A doença hepática gordurosa não-alcoólica já é considerada um problema de saúde pública, principalmente em pacientes com obesidade severa. OBJETIVOS: O objetivo do presente estudo foi investigar os diferentes escores de bioquímiosa disponíveis e determinar qual deles poderia servir melhor como uma ferramenta de avaliação da NAFLD em uma população de obesos. MÉTODOS: Este é um estudo transversal de pacientes obesos. Todos os pacientes foram avaliados com parâmetros laboratoriais séricos 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Goday et al 11 evaluated if HP eradication treatment could influence the evolution of weight loss and metabolic markers after bariatric surgery and found that HP-treated patients had higher weight loss and higher reduction of triglycerides and glucose levels. Moreover, the impact of HP has been evaluated on the incidence of gallstone formation after SG and found anti-HP antibody seropositive to be associated with cholelithiasis 14,29 . Its relation to gastroesophageal reflux disease (GERD) has also been explored, but despite no association with the incidence of de novo GERD, improvement of symptoms was higher in those with HP-confirmed eradication than in those without HP infection.…”
Section: Discussionmentioning
confidence: 99%
“…Goday et al 11 evaluated if HP eradication treatment could influence the evolution of weight loss and metabolic markers after bariatric surgery and found that HP-treated patients had higher weight loss and higher reduction of triglycerides and glucose levels. Moreover, the impact of HP has been evaluated on the incidence of gallstone formation after SG and found anti-HP antibody seropositive to be associated with cholelithiasis 14,29 . Its relation to gastroesophageal reflux disease (GERD) has also been explored, but despite no association with the incidence of de novo GERD, improvement of symptoms was higher in those with HP-confirmed eradication than in those without HP infection.…”
Section: Discussionmentioning
confidence: 99%
“…Esta doença é caracterizada pelo acúmulo excessivo de lipídeos dentro das células funcionais hepáticas, excluídas as causadas pelo excesso de álcool e outras doenças hepáticas. A sua gravidade é tida pelo fato de que é uma doença silenciosa que pode evoluir para cirrose hepática e mais agressivamente, para uma insuficiência hepática com necessidade de transplante (SILVA et al, 2021).…”
Section: Desenvolvimentounclassified
“…The World Health Organization (WHO) has one of the most comprehensive definitions of quality of life (QoL), which encompasses several functional domains. The self-perception of one's social context, goals, expectations, and concerns are concepts related to the QoL that affect the physical, psychological, and social domains of health 29 . These specific domains have been widely defined as “health-related quality of life” 16 .…”
Section: Introductionmentioning
confidence: 99%